A Model of Cigarette Advertisement Policy in Preventing Children Smoking Habits in Palu City, Indonesia: A Systematic Review - Muhammad Ryman Napirah1,2, Ridwan Amiruddin3, Sukri Palutturi4, Stang5, Vidyanto6, Rosmala Nur7, Muh (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: The high prevalence of smokers in Indonesia has led the government to issue various policies.One of the policies issued by the government to reduce or limit the prevalence is the cigarette advertisementpolicy. The purpose of this systematic review is to develop a model of cigarette advertisement policy inpreventing children smoking habits in Palu City, Indonesia.Method: This research used a systematic literature review. Various references were collected from onlinedatabase including reports, journals, and books in the last 10 years. The journals were mostly from thescholarly journals. The articles were screened according to the research objectives. The keywords used arecigarette advertisement policy and children smoking habits.Results: This study showed that the use of a model of cigarette advertisement policy is very effectivein preventing children smoking habits. Cigarette advertisement regulation policy is the government’scommitment to protect children, as an effort to protect the younger generation from cigarette advertisementsthat are intense and have a very large influence on smoking behavior. Cigarette advertisements are proven toencourage children to try cigarettes, repeating the behavior so that it eventually becomes a habit.Conclusions: This paper concludes that amodel using cigarette advertisement policy iseffective for prevent children smoking habits.Further recommendation will be provided.